The Effect of Leadership Style to the Company Performance in PT Tera Multi Wahana, Indonesia Based on 7S Mckinsey Theory - Georgio Hutabarat, Mikhael Evert; Lantu, Donald Crestofel (Journal of Business and Management, 2014)
- In this study, researchers analyzed about the leadership style of the leader who built that own business and has a leadership style that is unique and different from other leaders. To see how much influence the leadership style in the company of researchers using the McKinsey 7s theory where the theory can provide an assessment of the power of a leader's style and impact on the performance of the company. With the results of the analysis of PT Astra International were formed questions for PT Tera Multi Wahana. In addition to the question researchers also compared the Astra with Tera when their leaders set up a new company. From the analysis of PT Tera Multi Wahana the impact of Ramos Sihombing led a major have influence on his employees. This is seen from the view of the staff against his self and the impact of making them work in accordance with what had been determined by the company.Keywords: human resource, leadership, 7s McKinsey Theory, entrepreneurial leader,Â  servant leadership